Teaching in tiny letters: Eliyyah ben Berekhyah ha-Naqdan’s way of teaching as displayed in MS Biblioteca Apostolica Vaticana ebr. 14 - Liss, Hanna (Corpus Masoreticum working papers, 2022)
This paper deals with the Masorah and masora figurata illustration displayed on fol. 196r in MS Biblioteca Apostolica Vaticana ebr. 14. The scribe - Eliyyah ben Berekhyah ha-Naqdan - designed a tower that refers to the conquest of the territories and the cities that are recounted at the end of parashat Maṭṭot. The peculiarity of this figurative illustration lies in the fact that it does not only encompass masoretic material related to the biblical text, but also integrates the scribe’s explanation on the exegetical and halakhic relevance of a masora parva note, in which he took up various Bible commentaries and related them to a source introduced as ‘Midrash Harninu.’ This article explains the mise-en-texte on this folio as well as the masoretic notes displayed in detail, and discusses the Midrash Harninu source reference with regard to the question as to which extant the pesiqta-literature was known in Northern France (especially in the Anglo-Norman region). In addition, it will be debated that Eliyyah’s masora figurata illustrations did not simply serve as decorative elements but fulfilled educational purposes. The manuscript, Vat. ebr. 14, thus, could have been used as a ‘class-book’ for Bible teachers and students alike.